A review of Open Defecation (OD) in Indonesia and the control with logic model - Kartika Sari, Amalia Fitri; R., Azizah; Jalaludin, Juliana; Rahmawati, Isnaini; Sulistyorini, Lilis; Yudhastuti, Ririh; Sumantri, Arif; Jauharoh, Siti N. A.; Zulkarnain, Oryza Filial; Rizaldi, Muhammad Addin (Faculty of Medicine and Health Sciences, 2022)
In 2015, Indonesia was ranked as the second-highest, with a percentage of 12.9%. Open Defecation Free (ODF) in Indonesia is still a problem, 33 out of 34 provinces in Indonesia are still not 100% verified as ODF. The purpose of this study is to make a management control of OD behaviour in Indonesia. This study’s literature was collected using Google Scholar and Pubmed search engines by entering keywords open defecation Indonesia, and buang air besar sembarangan. From review of published literature, it is found that several factors cause people to practice OD, namely environmental, socio-cultural, and economic factors. These factors become the basis for making OD model control with a logic model. The program was made with a button-up approach carried out through several activities, namely approaches to community leaders, youth, and local communities, monitoring potential areas for OD practice and cross-sector coordination, and making regional regulations.